The Association between Depression, Self-efficacy, and Health-related Quality of Life Among Chinese Patients Undergoing Their First Percutaneous Coronary Intervention - Li Cheng; Wen-Ru Wang; Lotta Wikström; Jan Mårtensson (Asian Journal of Social Health and Behavior)
Introduction: The demand for percutaneous coronary intervention (PCI) has been steadily increasing along with the number of patients with coronary heart disease (CHD) in China. However, there is a lack of studies investigating health-related quality of life (HRQoL), self-efficacy, and depression among Chinese patients undergoing their first PCI. The aim of this study was to explore the association between depression, self-efficacy, and HRQoL among Chinese patients with CHD undergoing their first PCI. Methods: In this cross-sectional study, 212 Chinese patients with CHD who underwent their first PCI were recruited through convenience sampling from October 2019 to March 2020. HRQoL, self-efficacy, and depression were assessed using the Seattle Angina Questionnaire, Cardiac Self-Efficacy Scale, and Short-Form Cardiac Depression Scale, respectively, along with the collection of patients’ sociodemographic and clinical information. Results: Among the 212 participants, the average age was 59.82 years, and 145 (68.4%) were male. The average scores for self-efficacy, depression, and HRQoL were 33.49 (±10.28), 16.14 (±6.12), and 328.33 (±62.55), respectively. Among the 212 patients who underwent PCI, 134 (63.21%) were found to have depression symptoms according to the cutoff score of 14. A higher body mass index, a diagnosis of acute coronary syndrome, fewer years of CHD diagnosis, the absence of symptoms of depression and greater self-efficacy were significantly positively associated with HRQoL. In total, these variables explained 37.2% of the variance in HRQoL. Conclusion: This study revealed that the HRQoL of patients in this group needs to receive more attention. A comprehensive secondary prevention intervention for CHD patients undergoing their first PCI should emphasize mitigating depression and positively influencing their self-efficacy.